The Exchange Rate Exposure of Chinese Companies - WANG, JING (2008)
This study shows the extent of and reasons for foreign exchange exposure in Chinese companies. The results show that only 5 percent of sample firms have significant exposure to exchange rate fluctuations. This study examines the determinants of exchange rate exposure of a sample of 100 Chinese firms quoted on the Shanghai Stock Exchange 180 Share Index. Amongst those firms which have a significant exposure there is evidence to suggest that smaller firms and those with high leverage and high liquidity are more exposed to exchange rate risk. This study reports that Chinese stock market has some limitations which make the research results a little bit biased.